2012
DOI: 10.1080/00224545.2011.565384
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Right-Wing Authoritarianism via Personality and Dangerous World Beliefs: Direct, Indirect, and Interactive Effects

Abstract: In an Italian sample (N = 483, 78.23% women, mean age = 27.61 years old), we used structural equation modeling with latent variables and interactions to analyze the direct, indirect, and interactive effects exerted on right-wing authoritarianism (RWA) by the Big Five factors of personality and by dangerous world beliefs (DWB). Openness, Neuroticism, and Conscientiousness exerted direct effects on RWA; the first two relationships were partially mediated by DWB. Most importantly, the relationship between DWB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
4
11
0
1
Order By: Relevance
“…Discussing these findings, Van Hiel and De Clercq () concluded that RWA should be considered a “good for the self” construct, in that it “buffers the effects of facilitators of mental distress on actual experienced mental distress” (p. 47; however, for results inconsistent with this conclusion, see Duriez, Klimstra, Luyckx, Beyers, & Soenens, ). Moreover, our results have been substantially consistent with those stemming from Dallago and colleagues' (Dallago & Roccato, ; Dallago et al., , ) converging cross‐section analyses on the moderator role of the relationship between perceived threat to safety and RWA, played by Openness to experience, a personality trait which negatively correlates with RWA. Finally, they indirectly supported the idea of linking the literature on RWA with that on the CCM, in that psychological research showed that threat stemming from criminality undermines people's perceived control over the social world (Jackson, ; Perry & Sibley, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Discussing these findings, Van Hiel and De Clercq () concluded that RWA should be considered a “good for the self” construct, in that it “buffers the effects of facilitators of mental distress on actual experienced mental distress” (p. 47; however, for results inconsistent with this conclusion, see Duriez, Klimstra, Luyckx, Beyers, & Soenens, ). Moreover, our results have been substantially consistent with those stemming from Dallago and colleagues' (Dallago & Roccato, ; Dallago et al., , ) converging cross‐section analyses on the moderator role of the relationship between perceived threat to safety and RWA, played by Openness to experience, a personality trait which negatively correlates with RWA. Finally, they indirectly supported the idea of linking the literature on RWA with that on the CCM, in that psychological research showed that threat stemming from criminality undermines people's perceived control over the social world (Jackson, ; Perry & Sibley, ).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, among researchers there is no agreement on the “goodness for the self” of RWA: According to Van Hiel and De Clercq () and to Dallago and colleagues (Dallago et al., , ; Dallago & Roccato, ), RWA is a psychological variable helping people cope with stress, while according Duriez and colleagues (), it is not such a psychological variable. As a matter of fact, these researchers' did not assess coping directly: Thus, their conclusions have been merely inductive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the motivational goals described in the DPM are closely related to the sociopolitical context. Along similar lines, recent research has also indicated that openness to experience moderates the relationship between dangerous worldview and RWA (Dallago, Mirisola, & Roccato, 2012;Dallago & Roccato, 2010), and that particular authoritarian concerns can differ depending on socioeconomic status (Napier & Jost, 2008). Future research could expand upon the contribution we make here (in showing the DPM is predictive of distinct policy domains) by also examining the moderating effects of sociostructural and individual factors.…”
Section: Caveats and Conclusionsupporting
confidence: 55%
“…Our study suggested some interesting ideas for further research. First, some authors conceived authoritarianism as being a ‘good for the self’ construct (Dallago, Mirisola, & Roccato, , ; Dallago & Roccato, ; Van Hiel & De Clercq, ). Accordingly, authoritarianism may be considered to be an anxiety buffer (Greenberg et al, 1990), in that by definition, it should promote the ‘oneness’ and the ‘sameness’ of the society in which people live.…”
Section: Discussionmentioning
confidence: 99%